2021
DOI: 10.3390/ijerph18147252
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Age-Friendly City on Older People’s Continuity and Life Satisfaction

Abstract: According to continuity theory, successful aging is promoted when older people are able to continue familiar activities as a way to maintain self-identity. The purpose of this study was to examine the importance of both external resources provided by Taipei city and older adults’ internal resources in internal and external continuity and life satisfaction. The data were from the 2019 Taipei City Senior Citizen Condition Survey acquired through face-to-face interviews. Only the community-based sample without di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
6
0
2
Order By: Relevance
“…Community environment was another residence condition that increased life satisfaction in old age the most, in line with the literature [ 16 , 17 , 31 ]. Older adults’ community environment is often kept sanitary and clean so that people can enjoy a healthy and comfortable environment.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Community environment was another residence condition that increased life satisfaction in old age the most, in line with the literature [ 16 , 17 , 31 ]. Older adults’ community environment is often kept sanitary and clean so that people can enjoy a healthy and comfortable environment.…”
Section: Discussionsupporting
confidence: 83%
“…Notably, as the perspective on life in old age has become more realistic, efforts to understand and analyze various aspects related to life satisfaction in the elderly have greatly increased. Studies have identified the following factors related to life satisfaction in old age: health status [ 9 , 10 ], economic status [ 11 ], leisure activities, social participation such as volunteering [ 12 , 13 ], social relationships [ 14 , 15 ], living environment [ 16 , 17 ], computer use [ 18 ], employment status [ 19 ], and demographic characteristics [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the evaluation of urban facility friendliness for the elderly is still hardly quantitative and has not been grasped on the level of comprehensive evaluation, according to multiple aspects and indices in previous studies [17][18][19][20][21][22][23][24][25][26][27][28][29], which have mainly been based on the subjective satisfaction evaluation of indexes from different investigators (experts, officials, residents, etc.). The main focus of related research has been analyzing the differences between the ratings of residents with different socio-demographic characteristics as well as the impact of other factors (e.g., the health status, happiness, well-being, and quality of life) involving older residents on their perception of friendliness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The psychological well-being of middle-aged and older people can be improved by creating an environment that is age-friendly [ 8 – 12 ]. Because a community that recognizes and accommodates the needs of frail older adults can provide a protective buffer that will allow these individuals to remain in their homes for a longer period of time [ 13 ].…”
Section: Introductionmentioning
confidence: 99%